Patterns of sexualised recreational drug use and its association with risk behaviours and sexual health outcomes in men who have sex with men in London, UK: a comparison of cross-sectional studies conducted in 2013 and 2016. (19th November 2019) - Curtis, Tyrone J; Rodger, Alison J; Burns, Fiona; Nardone, Anthony; Copas, Andrew; Wayal, Sonali
Abstract : Objective: London has one of the highest identified prevalence of chemsex (sexualised recreational drug use) among men who have sex with men (MSM) in Europe. We examine MSM's patterns of chemsex and its association with HIV/STI risk behaviours, STI diagnoses and sexual healthcare-seeking behaviours, including if HIV testing behaviour met UK national guidelines (three monthly if engaging in chemsex). Methods: Cross-sectional survey data from 2013 (n=905) and 2016 (n=739) were collected using anonymous, self-administered questionnaires from MSM recruited in commercial gay venues in London, UK. Descriptive and multivariable analyses, stratified by self-reported HIV status, were conducted. Adjusted prevalence ratios (aPR) with 95% CIs were calculated. Results: Comparing the 2013 and 2016 surveys, chemsex prevalence in the past year remained stable, in both HIV-negative/unknown-status MSM (20.9% in 2013 vs 18.7% in 2016, p=0.301) and HIV-positive MSM (41.6% in 2013 vs 41.7% in 2016, p=0.992). Combined 2013–2016 data showed that compared with other MSM, those reporting chemsex were more likely to report HIV/STI risk behaviours, including condomless anal intercourse with serodifferent HIV-status partners (HIV-negative/unknown-status men: aPR 2.36, 95% CI 1.68 to 3.30; HIV-positive men: aPR 4.19, 95% CI 1.85 to 9.50), and STI diagnoses in the past year (HIV-negative/unknown-status men: aPR 2.10, 95% CI 1.64 to 2.69; HIV-positive men: aPR 2.56, 95% CI 1.57 to 4.20). 68.6% of HIV-negative/unknown-status men reporting chemsex attended sexual health clinics and 47.6% had tested for HIV more than once in the past year. Conclusions: Chemsex in London MSM remained stable but high, particularly among HIV-positive men. Irrespective of HIV status, chemsex was associated with engagement in HIV/STI risk behaviours. Frequency of HIV testing in the past year among HIV-negative/unknown-status men was below national recommendations. Promoting combination prevention strategies, including three monthly HIV/STI testing, access to pre-exposure prophylaxis/antiretroviral treatment and behavioural interventions among MSM reporting chemsex, remains vital to address sexual health inequalities in MSM.